Learn Questions from a handpicked tutor in LIVE 1-to-1 classes

# Identify all of the root(s) of g(x) = (x^{2} - 3x - 4)(x^{2} - 4x + 29).

**Solution:**

Given: Function g(x) = (x^{2} - 3x - 4)(x^{2} - 4x + 29)

Let us first consider x^{2} - 3x - 4

= x^{2} + 1x - 4x - 4

= x(x + 1) - 4(x + 1)

= (x + 1)(x - 4)

Now let us consider x^{2} - 4x + 29

First group the terms with variable on LHS and move the constant on the other side

x^{2} - 4x = -29

Add 4 on both sides

x^{2} - 4x + 4 = -29 + 4

x^{2} - 4x + 4 = -25

It can be written as perfect squares

(x - 2)^{2} = -25

We know that

i =√1

Take square root on both sides

x - 2 = ± 5i

x = 2 ± 5i

So we get,

x = 2 + 5i and x = 2 - 5i

g(x) = (x + 1)(x - 4)(2 + 5i)(2 - 5i)

Therefore, the roots are (x + 1), (x - 4), (2 + 5i), and (2 - 5i).

## Identify all of the root(s) of g(x) = (x^{2} - 3x - 4)(x^{2} - 4x + 29).

**Summary:**

All the root(s) of g(x) = (x^{2} - 3x - 4)(x^{2} - 4x + 29) are (x + 1), (x - 4), (2 + 5i), and (2 - 5i).

Math worksheets and

visual curriculum

visual curriculum